Coupling of Surface Plasmon Modes and Refractive Index Sensitivity of Hollow Silver Nanoprism. Issue 1 (December 2018) - Zhang, K.; Lu, D.; Da, B.; Ding, Z.
Abstract Localized surface plasmon (LSP) modes depend strongly on the morphology of nanoparticle and the surrounding dielectric medium. The hollow nanostructure provides a new way to modulate the surface plasmon modes due to the additional cavity surface. In this work, we study systematically the multipolar surface plasmon modes of hollow silver nanoprism (HSN) by simulation of electron energy loss spectroscopy (EELS) spectra based on the boundary element method (BEM). Herein the effects of the cavity size and position are taken into account. The LSP modes of HSNs are compared with those of perfect silver nanoprism (SN). The red-shift behaviors of multipolar modes can be found as increasing the cavity size. ModesA andC have similar red-shift tendency and obey the plasmon ruler equation, which can be explained by dipole-dipole coupling mode. Meanwhile, the degenerate modes will be split by changing the cavity position, and opposite shift tendencies of split degenerate states are observed. These are caused by different coupling nature of degenerate modes. Moreover, high refractive index sensitivity (RIS) can be obtained for HSN by changing the cavity size and position.